EVALUATION OF THE FUNGUS Sporothrix insectorum (Hoog and Evans) ON THE LACE BUG Leptopharsa gibbicarina (Froeschner) IN AFRICAN PALM - ORDÓÑEZ, ANA ISABEL; GENTY, PHILLIPE (Revista Colombiana de Entomología, 1989)
Foliar mildew complex on African Oil Palm (association of Leptinotarsa gibbicarina (Froeschner) Hemiptera: Tingidae with the plant pathogen Pestalotiopsis spp.) is an endemic problem in the Central and Northern regions of Colombia. This abnormality is responsible for reductions up to 60°/o in yields. The entomopathogenic S. insectorum was found controlling up to 98°/o the lacewing bug L. hevea in rubber plantations of Brazilian Amazonas. This fungus was introduced into Colombia by Indupalma, San Alberto (Cesar), to test against L. gibbicarina; comparing the growth of this fungus in four media (Sabourand, maltose, agar plus 1°/o yeast extract SDA; potato, dextrosa, agar PDA; agar plus pandit (mineral sales); semisynthetic salt enrich medium and the commercial medium 5467, specific for entornopathogens), under a completely randomized factorial design with four replicates in which two strains were subjected to 20, 27 and 30°C. It was found that S. insectorum grey,/ well in all the tested media at 27 and 30°C (65% R.H.), being the optima] temperature 27°C. Testing pathogenicity under laboratory conditions using five conidial concentrations (10, 105, 106, 107, 108) on 100 adults of L. gibbicarina per treatment, under a completely randomized design with four replications, it was found a positive effect at all concentrations in controlling the insects, when they were compared to the control (10 ml of water) the porcentages of mortality were: 1.3, 73.5, 73.4 and 72.2°/o showing no significant differences between different concentration. To test the pathogenicity of the two strains of fungi under fields conducting a randomized design was used with the same concentrations and replication as before but using 100 insects per treatment which were settled up in a palm leaf inside a screen cage (1,2 m x 40 cm diameter). The differences in the percentage of mortality between the treatments (concentrations) and the control were highly significant for both strains. For practical propones, it advisable to use 107 to 108 conidia/ml of fungy. The results obtained showed the great possibility of using S. insectorum to 'reach a good control of L. gibbicarina in African Oil Palm. However, more research should be done in other agroecological areas and perhaps in Tingidae of other crops.